A monolithic mixed matrix membrane based on silver nanoparticle/nylon‐6 nanocomposite: A novel coating for stir bar sorptive extraction of organophosphorus pesticides. Issue 6 (15th June 2021) - Ayazi, Zahra; Shekari Esfahlan, Fatemeh
Abstract: In this research, a novel monolithic mixed matrix membrane based on silver nanoparticles reinforced nylon 6 was prepared by in situ reduction of silver nitrate salt in a formic acid solution of nylon 6. The phase separation method was employed to deposit prepared nanocomposite onto a stainless steel substrate. The characterization of nylon 6 and silver nanoparticles/nylon 6 nanocomposite coated stir bars were conducted applying scanning electron microscopy, X‐ray diffraction, and energy dispersive X‐ray spectroscopy. The prepared stir bar was employed for the stir bar sorptive extraction of organophosphorus pesticides such as ethion, phosalone, and chlorpyrifos in environmental water samples applying gas chromatography with mass spectrometry. The effect of the silver nanoparticles doping level in the nanocomposite on the extraction efficiency of the monolithic mixed matrix membrane was studied. Multivariate optimization based on the central composite design was employed to study and optimize essential parameters affecting the extraction and elution steps. The limits of detection were 0.2 and 0.3 ng/mL and the linear dynamic ranges were in the concentration range of 0.7‐1000 and 1–1000 ng/mL for all analytes. The method precision based on relative standard deviation by performing six replicates ranged from 2.4 to 7.4% for spiked distilled water (100 ng/mL).